Toxic properties of iron oxide nanoparticles functionalized with citric acid as a new radiographic contrast enhancer / Nornaizie Che Nor Din - Che Nor Din, Nornaizie (2015)
Engineered nanoparticles have been extensively explored in various biomedical settings including nanoparticulate imaging agents due to its promising benefits to mankind. Iodine-intolerance patients have caused alarming concerns in searching new contrast media with lower toxicity effect. However, proper potential mechanism of nanoparticles has yet to be fully established despite its early acceptance and emerging usage. By using animal model system, our aim is to assess acute nanotoxicity of 14 nm iron oxide nanoparticles (IONPs) coated with citric acid in comparison to iodine. 18 male Wistar Rats were used in order to explore the underlying toxicity of IONPs in liver tissues. .OH free radicals were elucidated by using reactive oxygen species (ROS) production assay and western blotting for the presence of p53 protein expression. The results revealed coated IONPs produced higher ROS level compared to iodine, however no statistical significant were observed. It can be hypothesized that higher amount of antioxidant has been produced by rats in iodine group in correlation to combat higher amount of ROS produced before assayed was conducted. Stronger expressions of the p53 protein from the coated IONPS groups were further observed. Expression of p53 protein suggested initiation of antioxidants production by the protein to ameliorate intracellular ROS production to further achieve normal redox balance in curtailing further damage. The outcomes highlighted that short-term administration of IONPs with functionalization surfaces are safe to be applied as radiographic contrast enhancer. NANOTOXICITY ASSESSMENT OF IRON OXIDE NANOPARTICLES